Estrogen receptor beta promotes endometriosis progression by upregulating CD47 expression in ectopic endometrial stromal cells. (June 2022) - Hu, Laihua; Zhang, Jinghe; Lu, Yichen; Fu, Binqing; Hu, Weiping
Abstract: Endometriosis is a common estrogen-dependent gynecological disorder that is characterized by endometrial-like tissue being found at extrauterine sites. Aberrant expression and activation of estrogen receptor beta (ERβ) in ectopic endometrium are involved in endometriosis development. Here, we used primary tissues and cells from endometriosis patients to investigate the molecular mechanisms involved in ERβ's contribution to endometriosis progression. Through RNA-seq, quantitative PCR, and immunohistochemistry analysis, we found that ERβ expression is related to the severity of endometriosis; specifically, the ratio of ESR2/ESR1 in ectopic tissues was positively correlated with the severity of endometriosis, which suggests that ERβ has a predominant role in endometriosis progression. Furthermore, we found that ERβ could bind to the CD47 promoter, increasing CD47 expression levels. CD47 is a critical molecule in "don't eat me" signaling. These data highlight the importance of the ERβ-CD47 axis in the pathogenesis of endometriosis. We believe targeting CD47 may be a novel therapeutic approach for treating endometriosis and other ERβ-associated diseases. Graphical Abstract: ga1 Highlights: The radio of ERβ/ERα is a key indicator for the progression of endometriosis. CD47 is elevated in ectopic endometrial stromal cells. ERβ regulates CD47 expression by directly binding to the promoter of CD47. Targeting the CD47 may represent a promising therapeutic alternative for the treatment of endometriosis in the future.